The Paracrine Effect of Transplanted Human Amniotic Epithelial Cells on Ovarian Function Improvement in a Mouse Model of Chemotherapy-Induced Primary Ovarian Insufficiency - Xiaofen Yao; Yuna Guo; Qian Wang; Minhua Xu; Qiuwan Zhang; Ting Li; Dongmei Lai (Hindawi Limited, 2016)
Human amnion epithelial cells (hAECs) transplantation via tail vein has been reported to rescue ovarian function in mice with chemotherapy-induced primary ovarian insufficiency (POI). To test whether intraperitoneally transplanted hAECs could induce therapeutic effect and to characterize the paracrine effect of transplanted hAECs, we utilized a chemotherapy induced mice model of POI and investigated the ability of hAECs and conditioned medium collected from cultured hAECs (hAECs-CM) to restore ovarian function. We found that transplantation of hAECs or hAECs-CM either 24 hours or 7 days after chemotherapy could increase follicle numbers and partly restore fertility. By PCR analysis of recipient mice ovaries, the presence of SRY gene was only detected in mice transplanted with male hAECs 24 hours following chemotherapy. Further, the gene expression level of VEGFR1 and VEGFR2 in the ovaries decreased, although VEGFA increased 2 weeks after chemotherapy. After treatment with hAECs or hAEC-CM, the expression of both VEGFR1 and VEGFR2 increased, consistent with the immunohistochemical analysis. In addition, both hAECs and hAECs-CM treatment enhanced angiogenesis in the ovaries. The results suggested that hAECs-CM, like hAECs, could partly restore ovarian function, and the therapeutic function of intraperitoneally transplanted hAECs was mainly induced by paracrine-mediated ovarian protection and angiogenesis.